Novel genes involved in vascular dysfunction of the middle temporal gyrus in Alzheimer’s disease: transcriptomics combined with machine learning analysis - Meiling Wang; Aojie He; Yubing Kang; Zhaojun Wang; Yahui He; Kahleong Lim; Chengwu Zhang; Li Lu (Neural Regeneration Research)
Studies have shown that vascular dysfunction is closely related to the pathogenesis of Alzheimer’s disease. The middle temporal gyrus region of the brain is susceptible to pronounced impairment in Alzheimer’s disease. Identification of the molecules involved in vascular aberrance of the middle temporal gyrus would support elucidation of the mechanisms underlying Alzheimer’s disease and discovery of novel targets for intervention. We carried out single-cell transcriptomic analysis of the middle temporal gyrus in the brains of patients with Alzheimer’s disease and healthy controls, revealing obvious changes in vascular function. CellChat analysis of intercellular communication in the middle temporal gyrus showed that the number of cell interactions in this region was decreased in Alzheimer’s disease patients, with altered intercellular communication of endothelial cells and pericytes being the most prominent. Differentially expressed genes were also identified. Using the CellChat results, AUCell evaluation of the pathway activity of specific cells showed that the obvious changes in vascular function in the middle temporal gyrus in Alzheimer’s disease were directly related to changes in the vascular endothelial growth factor (VEGF)A–VEGF receptor (VEGFR) 2 pathway. AUCell analysis identified subtypes of endothelial cells and pericytes directly related to VEGFA–VEGFR2 pathway activity. Two subtypes of middle temporal gyrus cells showed significant alteration in AD: endothelial cells with high expression of Erb-B2 receptor tyrosine kinase 4 (ERBB4high) and pericytes with high expression of angiopoietin-like 4 (ANGPTL4high). Finally, combining bulk RNA sequencing data and two machine learning algorithms (least absolute shrinkage and selection operator and random forest), four characteristic Alzheimer’s disease feature genes were identified: somatostatin (SST), protein tyrosine phosphatase non-receptor type 3 (PTPN3), glutinase (GL3), and tropomyosin 3 (PTM3). These genes were downregulated in the middle temporal gyrus of patients with Alzheimer’s disease and may be used to target the VEGF pathway. Alzheimer’s disease mouse models demonstrated consistent altered expression of these genes in the middle temporal gyrus. In conclusion, this study detected changes in intercellular communication between endothelial cells and pericytes in the middle temporal gyrus and identified four novel feature genes related to middle temporal gyrus and vascular functioning in patients with Alzheimer’s disease. These findings contribute to a deeper understanding of the molecular mechanisms underlying Alzheimer’s disease and present novel treatment targets.